Measurements of self-guiding of ultrashort laser pulses over long distances - Poder,K; Cole,JM; Wood,JC; Lopes,NC; Alatabi,S; Foster,PS; Kamperidis,C; Kononenko,O; Palmer,CA; Rusby,D; Sahai,A; Sarri,G; et al. (Plasma Physics and Controlled Fusion, 2017)
We report on the evaluation of the performance of self-guiding over extended distances with $f/20$ and $f/40$ focussing geometries. Guiding over $39\,mm$ or more than 100 Rayleigh ranges was observed with the $f/20$ optic at ${n}_{e}=1.5× {10}^{18}\,{cm}^{-3}$. Analysis of guiding performance found that the extent of the exiting laser spatial mode closely followed the matched spot size predicted by 3D nonlinear theory. Self-guiding with an $f/40$ optic was also characterised, with guided modes observed for a plasma length of $90\,mm$ and a plasma density of ${n}_{e}=9.5× {10}^{17}\,{cm}^{-3}$. This corresponds to self-guided propagation over 53 Rayleigh ranges and is similar to distances obtained with discharge plasma channel guiding.